Measure characterizations and properties of normal and regular lattices - Peter M. Grassi (International Journal of Mathematics and Mathematical Sciences)
Various equivalent characterizations of normality are considered and a measure theoretic definition is given for strongly normal lattices. Measure conditions related to the apace of σ-smooth, lattice-regular, 0−1 measures are noted which imply, or are equivalent to, the space being Hausdorff, regular, or prime complete.